Congenital Bilateral Ectropion in Collodion Baby: A Rare Case Report - Aruna K.R. Gupta; Kashyap Patel; Yashvi Nathwani; Nikunj Amin; KIshan Makwana (Delhi Journal of Ophthalmology)
A baby born with normal full term vaginal delivery to a healthy mother aged 30 years was admitted to Neonatal intensive care unit at our tertiary care centre. On ophthalmological examination, the patient had bilateral ectropion of both the upper and lower eyelids. The eyelashes of the lower eyelids were missing. There was no evidence of discharge, corneal opacities or keratitis. No other ocular abnormality was found. Collodion baby is a rare disease; and there is no established management protocol. We managed the patient conservatively by the use of 0.05 % Clobetasol ointment for local application over the eyelids and lubricant (Carboxy methyl cellulose 1%) eye drops. Thus, the case was managed successfully with no requirement for surgical intervention.